A macro‐element with bidirectional interaction for seismic analysis of unreinforced masonry walls. (10th February 2023) - Kesavan, Prabakaran; Menon, Arun
Abstract: Prior to implementing retrofitting measures for seismic action, it is necessary to evaluate the global capacity of unreinforced masonry (URM) buildings. Even with simplified assumptions, equivalent frame (EF) modeling adequately captures global responses and failure mechanisms in existing buildings, making it a popular modeling strategy among structural engineers. However, macro‐elements employed in the EF modeling of URM walls consider in‐plane (IP) and out‐of‐plane (OP) behaviors separately by decoupling their interaction and require independent verification for OP failure involving limit analysis. Such decoupling of interaction is justifiable if proper wall‐wall/wall‐floor connections and rigid‐diaphragm action of slabs are ensured; however, OP failure is likely a result of inadequate connections. Multiple components of ground motion excitation and plan eccentricity in buildings can activate bidirectional interaction in such circumstances. Due to OP damage, the interaction reduces the full IP strength of a URM wall, resulting in overestimating its lateral capacity. This paper proposes a frame‐like 3D macro‐element incorporating the effect of OP action on the IP shear response of URM piers under static and monotonic lateral loads. Only two parameters modifying IP shear stiffness and capacity are required to account for the interaction. Analytical expressions for the interaction parameters are proposed from a detailed micro‐modeling study. The paper also demonstrates, within the EF modeling, the applicability of the proposed macro‐element for seismic analysis of regular URM shear walls with openings.